(untitled) (Journal of Pharma Insights and Research, 2026)
A validated isocratic reversed-phase high-performance liquid chromatography assay was developed for the simultaneous determination of duloxetine hydrochloride and pregabalin in combined pharmaceutical formulations. Due to the absence of a conjugated ultraviolet chromophore in the aliphatic backbone of pregabalin, pre-column derivatization via nucleophilic acylation using benzoyl chloride under alkaline conditions was implemented to incorporate a benzoyl moiety, enabling sensitive spectrophotometric detection. Separation was achieved on an Agilent 1100 Series HPLC system equipped with a reversed-phase stationary phase maintained at 25°C, utilizing an isocratic mobile phase of methanol, acetonitrile, and water in a 50:20:30 (v/v/v) ratio at a flow rate of 1.0 mL/min. Spectrophotometric detection was carried out at 241 nm for duloxetine and 208 nm for the derivatized pregabalin. Duloxetine and pregabalin eluted at retention times of 2.564 min and 6.321 min, respectively, exhibiting sharp peak symmetry and baseline resolution. The assay was validated in compliance with ICH Q2(R1) guidelines. Calibration plots exhibited linearity across 5–25 µg/mL for both compounds with correlation coefficients of 0.999. Repeatability and intermediate precision showed relative standard deviations below 1.0%. Mean analytical recoveries across 80%, 100%, and 120% spike levels ranged from 99.32% to 99.89% for duloxetine and 99.69% to 99.99% for pregabalin. The method showed ruggedness and robustness against minor variations in organic composition and wavelength, confirming its suitability for routine quality control testing of both active ingredients